THE INFLUENCE OF HEALTH COACHING BASED ON THEORY OF HEALTH BELIEF MODEL TOWARDS BLOOD PRESSURE IN SELANTANG BERSINAR - Norma Cahyani; Suprihatin (Suluh Adiluhung Publisher (SAPub), 2025)
Hypertension is a chronic disease that causes complications of deadly diseases. Hypertension in the elderly is associated with the aging process that occurs in the body. Hypertension management is carried out pharmacologically and non-pharmacologically. Non-pharmacological management with lifestyle modification, diet, exercise and stress management. Hypertension management information can be through continuous health education with an approach to individuals in accordance with theory of Health Belief Model that health coaching can change behavior and improve the quality of elderly life. The objective was to determine the influence of health coaching towards reducing blood pressure to elderly in accordance with theory of Health Belief Model. Research method used a quasi-experimental pre and posttest without control group. The study was conducted in conjunction with the Selantang Bersinar learning process activities in Ngronggo Village from May to November 2023 with 25 elderly respondents using a purposive sampling technique. Health education was carried out through an approach to elderly individuals directly. The result of the normality test was normal, the statistical test used Paired sample t-test. The results of univariate analysis showed that the average difference in pretest and posttest systolic blood pressure was 16.36 and the difference in pretest and posttest diastolic blood pressure was 6.8. Using Paired sample t-test, the results of the bivariate analysis showed that there was an influence of health coaching based on theory of Health Belief Model towards systolic blood pressure and diastolic blood pressure with p value of 0.00. In conclusion, there was an influence of health coaching based on theory of Health Belief Model towards reducing blood pressure in Selantang Bersinar, Ngronggo Village. Furthermore, the elderly who have received health coaching can implement healthy lifestyle, hypertension management for the purpose of managing hypertension cases in the community and can transmit good knowledge to families and community to improve health of Indonesian people.